2011
DOI: 10.1080/08995605.2011.550222
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Expert Ratings and Self-Assessments of Situation Awareness During a Combat Fatigue Course

Abstract: The current study compared expert-observer ratings of situation awareness (SA) with subjective self-ratings of SA in Norwegian military academy cadets during a summer combat survival course. The cadets (N = 30) completed an 8-day combat survival course characterized by sleep and food deprivation, continuous operations, and altered circadian entrainment cues. Results indicated that self-ratings of SA did not correlate consistently with expert-observer SA ratings, and self-ratings were consistently higher than e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…This is in stark contrast with the team members' experiences, as their understanding in the CE condition is not significantly different from their understanding in the non-enriched CNE and DNE conditions, and significantly lower than in the DE condition (see Table A3 in Appendix A). This finding confirms previous work conducted in different contexts (Matthews et al, 2011;Salmon et al, 2006) that shows that the ratings of observers are typically not in line with the team members assessments, particularly not in situations of stress and time pressure.…”
Section: Situation Awareness Of the Observerssupporting
confidence: 88%
See 2 more Smart Citations
“…This is in stark contrast with the team members' experiences, as their understanding in the CE condition is not significantly different from their understanding in the non-enriched CNE and DNE conditions, and significantly lower than in the DE condition (see Table A3 in Appendix A). This finding confirms previous work conducted in different contexts (Matthews et al, 2011;Salmon et al, 2006) that shows that the ratings of observers are typically not in line with the team members assessments, particularly not in situations of stress and time pressure.…”
Section: Situation Awareness Of the Observerssupporting
confidence: 88%
“…Although literature is sparse, there is some previous work that suggests that team members in situation of stress and time pressure tend to rate their situational awareness higher than the observers do, and that the observers are not able to capture the differences and nuances of the team members' situational awareness (Matthews et al, 2011). Therefore, we hypothesize:…”
Section: Research Approachmentioning
confidence: 92%
See 1 more Smart Citation
“…They also state that character strengths are specific phenomenon that co-exists with goals, interests, and values. Research at the NMA during a combat fatigue course revealed that cadets lost both their situation awareness and their ability to focus on certain missions while being sleep deprived (Matthews, Eid, Johnsen, & Boe, 2011: Matthews, Martinez, Eid, Johnsen, & Boe, 2007. Avoiding this will be important for a military officer during a mission.…”
Section: Introductionmentioning
confidence: 99%
“…| is the probability of chunk being retrieved successfully; | is the probability of optimal rule being chosen; is the activation level of chunk; is the activation threshold; and is the cognitive level. SA assessment using observer and self-rating methods under extremely stressful and challenging training conditions was investigated in [73]. The results show that subjective SA measures are unlikely to produce valid estimates of SA under extreme conditions.…”
Section: B Qualitative Sa Methods 1) Sa For Pilotsmentioning
confidence: 99%